Nature Environment, Socioeconomic and Culture Value in Gunung Salak Endah Tourism - Bahagia Bahagia; Abdul Karim Halim; Leny Muniroh; Rimun Wibowo; Muhammad Shiddiq Ilham Noor; Iis Khaerunnisa Fitriani; Siti Nurkholipah; Shofa Mahartika (Universitas Pahlawan Tuanku Tambusai, 2022)
Nature demaged enable to stop nature tourism because touris rely on nature conservation. Tourist areas such as Wisata Gunung Salak Endah in Bogor are tours that make nature a tourist attraction so that natural preservation must be maintained. The purpose of this study is to find the economic values of nature tourism, cultural values, and efforts to maintain the sustainability of the natural environment. The research uses qualitative methods. While the selection of respondents was done purposively. Data collection is done by in-dept-interview, documentation and observation. The results show that nature tourism empowers the community by involving the community in management such as ticket sales and parking management. At the same time, it provides opportunities for the community to trade food and beverages by opening stalls in the area and outside the area. People can even sell various traditional foods, handicrafts and sell ornamental plants. All produce economic value. There is even a unification of music in this tourist area because there is a grandfather who plays the harp in the midst of beautiful nature so that it is a natural therapy to entertain and relieve stress. Plus there is no change in the culture and social of the community because the Sundanese people in the area know enough about the foreign culture of the visitors' language but do not adopt it. At the same time, they introduce Sundanese culture by speaking Sundanese when someone buys food and drinks. When visitors do not understand, then continue with Indonesian.